Treating grapes with a natural alkaline decoction prepared from (Salsola arbuscula Pall.) - Odinayev Mirzamad; Safarov Asqar (BIO Web of Conferences)
In the article, the methods of increasing the efficiency of drying, shortening the drying time and obtaining high-quality dried raisins have been achieved by processing the bunches of large-sized raisin varieties of grapes grown in the Republic of Uzbekistan in different ways. The location of the large cultivation is considered to be the hill slopes with good wind circulation, as well as these areas are considered to be optimal, as well as there is a lot of precipitation in early autumn. To eliminate these inconveniences, the process of drying grape bunches is the use of basic and energy-saving methods of processing agricultural products, Salsola arbuscula Pall, which grows in the natural steppe regions of “Surkhandarya” region, is used for grape bunches. Experiments were conducted to determine the optimal concentration of the natural alkaline decoction prepared from the plant.